Peran Pembelajaran Blended Learning melalui Whatsapp pada Anak Madrasah Ibtidaiyah Normal Islam Rakha di Masa Pandemi Covid-19 - Rif'atul Ajizah; Andi Prastowo (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
This research highlights the role of blended learning through whatsapp for the children of the Islamic Normal Islamic Madrasah Rakha Amuntai. This research aims to find out how the role of blended learning through whatsapp during the covid-19 pandemic is, the author chose this problem because online learning is still rampant for school children, especially here elementary school age children. The approach used in this research is qualitative, with interview and observation methods. This research interviewed 10 students and 10 parents of MI Normal Islam Rakha students. In addition, the authors made observations during the learning period. The objectives to be achieved in this scientific idea are to describe the role of blended learning, to know WhatsApp as an alternative in learning, and to learn blended learning through WhatsApp. The final conclusion obtained by learning with blended learning via whatsapp during the covid-19 pandemic was very helpful, namely combining limited face-to-face learning and online learning via whatsapp.